Tandem of Populism and Post-truth as the background of development of the modern democracy in Ukraine - Vira Dodonova (Cхід, 2019)
Political science theories and concepts that describe the real political process have always been the empirical basis for political philosophy. According to the author, the 2019 Ukrainian presidential election campaign can best be understood and described using the concepts of “populism” and “post-truth”. The paper analyzes the discourse of the concept of “populism”, and reveals its content and main features. The need to establish social supervision over the actions of the authorities as a means of countering populism is emphasized. Essential characteristics of the post-truth phenomenon are revealed. The theoretical chain of the terms “verity” – “truth” – “post-truth” is presented. The meme as a unit of post-truth is analyzed. The paper proves that it was the bundle of populism and post-truth that had been the background of the electoral consciousness where the manipulative election technologies of the presidential campaign in Ukraine unfolded.